2020
DOI: 10.5489/cuaj.6690
|View full text |Cite
|
Sign up to set email alerts
|

Could sublingual vaccination be a viable option for the prevention of recurrent urinary tract infection in Canada? A systematic review of the current literature and plans for the future

Abstract: (word count: 248) Introduction:  We conducted a systematic review to examine the role of a novel sublingual vaccine – Uromune – for prevention of recurrent urinary tract infection (rUTI) to understand its potential role for Canadian women suffering from rUTI. Methods: Databases were searched for studies published from 2010-2020 that investigated use of Uromune in management of rUTI.  Only original clinical studies which included use of Uromune as prophylaxis for uncomplicated rUTI in women that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Furthermore, our results are further supported by recently published data in common variable immunodeficiency subjects suffering from RRTIs, where MV130 treatment significantly reduced the number of episodes of respiratory infection, antibiotic uptake, and unscheduled medical visits (11). On the other hand, different retrospective and prospective studies indicate that MV140 protect women suffering from uncomplicated RUTI, increasing the probability of UTI-free status and/or reducing the frequency of UTIs (16)(17)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, our results are further supported by recently published data in common variable immunodeficiency subjects suffering from RRTIs, where MV130 treatment significantly reduced the number of episodes of respiratory infection, antibiotic uptake, and unscheduled medical visits (11). On the other hand, different retrospective and prospective studies indicate that MV140 protect women suffering from uncomplicated RUTI, increasing the probability of UTI-free status and/or reducing the frequency of UTIs (16)(17)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 87%
“…The rationale for using MV130 and MV140 daily for 3 months was supported by previous publications with both formulations (11,13,(16)(17)(18)(19)(20)(21)(22). We sought to determine the clinical benefit of MV130 in a cohort of patients with SAD and recurrent infections who underwent immunization with MV130 for 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MV140 (Uromune) is a polyvalent bacterial preparation based on whole heat-inactivated components used to prevent RUTIs ( 38 ). This sublingual vaccine is composed of bacteria causing the majority of RUTIs in Europe: 75% Gram-negative bacteria (25% Escherichia coli , 25% Proteus vulgaris and 25% Klebsiella pneumoniae ) and 25% Gram-positive bacteria ( Enterococcus faecalis ) ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…MV140, also known as Uromune, is a sublingual vaccine composed of a mixture of inactivated Escherichia coli , Klebsiella pneumoniae , Proteus vulgaris and Enterococcus faecalis currently pre-licensed in phase 3 stage. Although randomized placebo-controlled clinical trials are still underway, preliminary data from retrospective and prospective uncontrolled studies reported a significant efficacy of the vaccine to prevent recurrent UTIs in women between 16 and 97 years old [ 109 , 110 ]. However, the compliance of this treatment could be questioned considering the 3-month daily administration period.…”
Section: State Of the Art Of Vaccines And Mabs To Tackle Pseudomonas Aeruginosa And Escherichia Colimentioning
confidence: 99%